Effects of Taekwondo intervention on balance ability: A meta-analysis and systematic review - Zhengfa Han; Hanyu Ju (PLoS ONE, 2025)
Objective This study investigated the effects of Taekwondo interventions on balance ability through meta-analysis and systematic review. Additionally, an optimal intervention protocol was proposed based on subgroup analysis of single-leg stance outcomes to enhance the overall effect. Methods Systematic searches were conducted in Chinese (CNKI, WANFANG DATA), English (Web of Science, PubMed), and Korean (KISS, RISS, DBPIA) databases to identify randomized controlled trials (RCTs), pre-post studies, and cross-sectional studies (CSS) evaluating Taekwondo’s impact on balance. A total of 21 studies encompassing 972 participants were included. The risk of bias in the RCTs was assessed using the Cochrane Risk of Bias Tool version 2 (RoB 2.0), and the methodological quality of pre-post and cross-sectional studies was evaluated with the Methodology Index for Non-Randomized Studies (MINORS) criteria. Quantitative analyses focused on measures such as single-leg stance with eyes closed, marching in place with eyes closed, and assessments using the Win pod device. Qualitative analyses addressed other assessment methods. Results The overall risk of bias results for the included RCTs indicated that four studies were classified as high risk, while the remaining studies demonstrated some concerns regarding risk. The methodological quality of the included non-RCTs was assessed as moderate. Furthermore, the quantitative outcomes indicated that Taekwondo interventions significantly enhanced both static (single-leg stance with eyes closed; ES = 0.862, p<0.001) and dynamic (marching in place with eyes closed; ES = 0.296, p = 0.036) balance abilities. However, analysis using the Win pod device for static balance showed no significant improvement (p>0.05). Subgroup analysis for the single-leg stance with eyes closed demonstrated the most substantial effects in adults (ES = 1.191, p = 0.001) and females (ES = 0.786, p = 0.005). The most effective Taekwondo intervention featured a duration of 12 weeks (ES = 1.375, p = 0.002), a frequency of once per week (ES = 1.406, p = 0.003), and a times length of 60–70 minutes (ES = 1.028, p<0.001). Qualitative assessments supported these findings, indicating overall beneficial impacts on balance from Taekwondo training across various populations and evaluation methods. Conclusions In conclusion, Taekwondo interventions are effective for enhancing static and dynamic balance abilities, especially in adult females. It is recommended to follow a training protocol of 60–70 minutes per times, once weekly, for 12 weeks to optimize static balance improvements.